Zielonogórskie środowisko historyczne po 1945 roku - Dolański, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The years 2023 and 2024 bring important anniversaries for the Zielona Góra academic community of historians, and even more broadly for the entire academic community. It was 70 years ago that the State Archive in Zielona Góra and the Zielona Góra branch of the Polish Historical Society were founded, giving rise to the academic community in Zielona Góra. It was historians who, until the establishment of the Higher School of Engineering, later the Zielona Góra University of Technology, and the Teacher Training College, later the Higher School of Pedagogy, constituted the most academically active community in the city, and then had a significant impact on the development of the two universities and their respective academic communities.
Keywords: Zielona Góra; życie naukowe; historycy; academic community; historians